Limitation of Fuel Subsidy in Healthizing State Revenue and Expenditure Budget - Putra, Tamin Ripinra; Lestari, Maria Maya; Haryono, Dodi (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Fuel oil (BBM) subsidy policy in Indonesia has been an important element in economic policy since the era of President Soeharto's administration. Initially, this subsidy was aimed at maintaining energy price stability and protecting people's purchasing power, especially low-income groups. However, over time, fuel subsidies have created various economic and environmental problems, including a large burden on the State Revenue and Expenditure Budget (APBN), economic distortions, and obstacles to the renewable energy transition. This research uses a normative legal approach to analyze fuel subsidy policies within the framework of the welfare state in Indonesia, with the aim of formulating more effective regulations. The data used is primary, secondary and tertiary legal materials which are analyzed descriptively-analytically. The research results show that the fuel subsidy policy has not been effective and efficient, with most of the benefits being enjoyed by the middle and upper income groups, while those who should benefit, namely the poor, are left behind. Therefore, it is necessary to reformulate fuel subsidy policies with the principles of social justice, economic sustainability, transparency and accountability. Formulating more targeted policies, developing renewable energy, and implementing the principles of good governance will strengthen the welfare state and support more equitable and sustainable development.